Post Independence Playwriting in Ghana: A Critical Comparative Appraisal of the Dramatic Works of Asiedu Yirenkyi & Ben Abdallah - Akenoo, M.K. (University of Ghana, 2002)
Post-independence playwriting in Ghana is mainly characterized by experimentation and “avant-gardism” that can be geared towards the development of professional theatre. These characteristics are portrayed in the plays of new emergent playwrights like Efua Sutherland, Joe De Graft, Ama Ata Aidoo, Bill Marshall, Martin Owusu, Asiedu, Yirenkyi, and Ben Abdallah as compared to the pre-independence playwrights like Kobina Sekyi, F.K. Fiawoo and J.B. Danquah whose works were mainly patterned on Western direction and orientation. To this end, the works of the pre-independence playwrights constitute what can be aptly described as “closet drama” from the critical standpoint. Efua Sutherland pioneered and laid the foundation for professional playwriting and professional theatre in Ghana. This era saw the rapid development of professional theatre in Ghana. The first play written by Efua Sutherland, titled Foriwa, was produces shortly after Ghana’s independence in 1957. This was followed up later with Edufa and The Marriage of Anansewa respectively by the same playwright. The evolution and development of professional playwriting and professional theatre in Ghana came to its full apogee with the emergence of Asiedu Yirenkyi and Ben Abdallah on the Ghanaian playwriting scene. Their works, in terms of subject, theme, and style, are clear manifestation of playwriting, which is unique and distinct from their predecessors ‘of the pre-independence days. Basically, the two playwrights blend traditionalism with modernism in their writings; and furthermore, whilst Asiedu Yirenkyi searches for audience awareness, Ben Abdallah, an avant-garde playwright, is steeped in portraying, the “Abibigoro” concept in this persistent search for an African theatre.
MPhil.Theatre Arts
Keywords: Post Independence; Ghana; Playwriting; Dramatic Works; Asiedu Yirenkyi; Ben Abdallah